MANAJEMEN SARANA DAN PRASARANA SEKOLAH - Iskandar Iskandar; Rohiat Rohiat; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The general purpose of this research was compare the management of infrastructure and facilities in 02 primary schools and 06 primary schools Pondok Kelapa in the central of Bengkulu. This study uses a comparative approach to qualitative research. Subjects in this study is the principal. Data collection techniques used in this research is by interview, observation and documentation. The conclusion of this study indicate that both SD discount a lot of similarities in the management of facilities and infrastructure, among others: the planning done by the principal in accordance with the regulations, infrastructure procurement droping from the government, purchases, donations from parents, and make their own, an inventory of school facilities and the infrastructure has been done with the record book in the book inventory of goods, distribution is carried out directly and indirectly, maintenance of school facilities and infrastructure conducted regularly and incidental.